Analysis of Multilayered Power Module Packaging Behavior Under Random Vibrations - Liang, Di; Wu, Qiong; Ghaderi, Davood; Guerrero, Josep M. (Ieee-Inst Electrical Electronics Engineers Inc, 2020)
Solder joints are the critical components of the printed circuit boards (PCBs) in the moving electronic systems, such as satellites and automotive industries that are most vulnerable to accidental vibrations. Therefore, the reliability of these boards since they are designed to be used for long-time applications is important. Since the laboratory tests are time-consuming and require well-equipped and costly measurement devices, reliability tests are preferred to perform through the analytical methods. In this article, an analytical model based on the multilayer plate theory is presented for the random vibration analysis, and the results are obtained for the different vibration frequencies, including the natural vibration frequency. For the proposed model, the state of the PCB layer and the amount of the stress in the solder joints are investigated separately, and the normal and shear stresses are obtained through the combined sinusoidal-exponential equation. Results by the finite-element method (FEM) analysis show that the cracks form at the edge of the interconnection points of the board, and the solder and void formation and crack propagation appear in the corners of the PCB in frequencies closed to the natural vibration frequency. Reliability increases by the reduced solder height.
Keywords: Vibrations; Mathematical model; Stress; Loading; Strain; Load modeling; Soldering; Fatigue life; solder; vibration